Practical Application of Methods in Strategy-Based Analyzes - Nábrádi, András; Forest, David; Madai, Hajnalka; Bittner, Beáta; Kovács, Tünde Zita; Nagy, Adrián (International Journal of Engineering and Management Sciences, 2021)
Increasing environmental volatility is a growing challenge for companies and businesses. The speed of economic events is changing, and the risk of uncertainty is increasing, requiring business to take a new approach to strategic planning. In the design and forming of their strategy, both the factors of the external and internal environment and the analysis of their competitors can be based on well-chosen methods. We consider the review of these methods, their application in planning and educational practice. The aim of our work, in which we present the methods that underpin the strategy applied in both domestic and international practice. The analysis of the external environment illustrates the construction and applicability of an external factor analysis matrix based on traditional PEST analysis and the Porter's five-factor model. In the case of internal factor analysis matrix, we focus on the approach of method choice, and on the applicable methods, the importance of the resource-based approach, the analysis of key factors and the Porter value chain analysis matrix. The third pillar of the analysis that underpins the strategy is the matrix-based assessment of competitors. The applicability of the methods depends on the form of the enterprise, the field of activity and the nature of its activities, which is complicated by the emergence of new economic spheres (e.g.: sharing) and transformed power relations.